2008
DOI: 10.1172/jci32806
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-modified α-synuclein blocks chaperone-mediated autophagy

Abstract: Altered degradation of α-synuclein (α-syn) has been implicated in the pathogenesis of Parkinson disease (PD).We have shown that α-syn can be degraded via chaperone-mediated autophagy (CMA), a selective lysosomal mechanism for degradation of cytosolic proteins. Pathogenic mutants of α-syn block lysosomal translocation, impairing their own degradation along with that of other CMA substrates. While pathogenic α-syn mutations are rare, α-syn undergoes posttranslational modifications, which may underlie its accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
580
0
14

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 459 publications
(606 citation statements)
references
References 48 publications
12
580
0
14
Order By: Relevance
“…Such mishandling of aberrant proteins alters proteostasis and often leads to the precipitation of protein aggregates that contribute to neuronal demise [49]. The involvement of CMA in neurodegeneration is two-fold, as it contributes to the elimination of pathogenic proteins, but also often, becomes victim of the toxic effect of these aberrant proteins [50][51][52][53]. This dual role of CMA in neurodegenerative disorders makes it necessary to analyze the status of this autophagy pathway in disease in order to determine whether interventions aimed at enhancing CMA activity could be of potential value or not, depending on the degree of compromise of this pathway and the reversibility of the CMA blockage.…”
Section: Reduced Cma and Neurodegenerationmentioning
confidence: 99%
See 3 more Smart Citations
“…Such mishandling of aberrant proteins alters proteostasis and often leads to the precipitation of protein aggregates that contribute to neuronal demise [49]. The involvement of CMA in neurodegeneration is two-fold, as it contributes to the elimination of pathogenic proteins, but also often, becomes victim of the toxic effect of these aberrant proteins [50][51][52][53]. This dual role of CMA in neurodegenerative disorders makes it necessary to analyze the status of this autophagy pathway in disease in order to determine whether interventions aimed at enhancing CMA activity could be of potential value or not, depending on the degree of compromise of this pathway and the reversibility of the CMA blockage.…”
Section: Reduced Cma and Neurodegenerationmentioning
confidence: 99%
“…Dysfunction in CMA has been described in both familial [50,52,54,55] and sporadic [51,52] PD. In the case of familial PD, sequence analysis reveals the presence of CMA-targeting motifs in the majority of PD-related proteins, supporting an important role for CMA in the control of their intracellular levels ( Figure 2A).…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly CMA has been shown to degrade -synuclein [103]. However, the mutant, oligomeric or dopamine-treated -synuclein prevent its CMAmediated degradation by blocking uptake into lysosomes [111,112]. Winslow et al showed that -synuclein overexpression inhibited autophagosome formation in autophagy [113].…”
Section: Proteotoxic Stress In the Pathogenesis Of Diseases Not Formementioning
confidence: 99%